I28 Does age of onset affect the clinical phenotype and its progression in adult onset huntington's disease? An observational five year follow up study. (13th September 2016) - Bonello, Michael; Panicker, Jayachandran; Polydoros, Fotis; Davies, Rhys; Alusi, Sundus
Abstract : Background: It is well established that CAG repeat length affects age at onset (AAO) in HD. However, the relationships between AAO and HD clinical phenotype and disease progression are not clear. Clarity concerning these relationships may be useful in clinical practice, and crucial in designing clinical trials if disease-modifying effects are to be identified. Objectives: A. Establish whether the AAO, independent of CAG number, affects HD phenotype (motor, cognitive or behavioural). B. Determine whether the rate of disease progression differs across AAO groups, after adjusting for CAG repeat length. Methods: This observational study involved all patients given the HD diagnosis within two years of enrolment in Euro-HD at 2007 who had 2012 follow-up data. Baseline UHDRS motor sub-scores, behavioural and cognitive scores were analysed. Total Motor Score (TMS) and Total Functional Score (TFS) were used to study the rate of disease progression. Results: There were 118 patients, mean AAO of 42 years and mean CAG repeat length 45. Those with AAO of >45 had significantly worse cognitive function (measured by Stroop Colour Naming Test and Symbol Digit Modality Tests) and significantly worse balance (measured by Tandem Gait Scores). There was a trend for patients with younger AAO to have better Finger Tap Scores and TFC Scores and worse behavioural scores. AAO did not significantly affect rate of disease progression, measured by TMS and TFC. Conclusions: AAO can affect HD phenotype – an important aspect to consider when designing trials in drugs targeted at modifying cognitive decline and functional deterioration in HD.